KASBIY TAYYORGARLIK DARAJASINI SHAKLLANTIRUVCHI MUHIM MAVZULARNI O’QITISH METODIKASI - Tugalov, F.Q. (SCIENCE and SOCIETY, 2019)
The article is devoted to the study of he content of integrated knowledge in Physics and Chemistry. On the basis of teaching Physics, it is shown, the development of knowledge on a high level, expansion OFoutlook and mastering representation about a physical picture of the world.
Keywords: Physics; Chemistry; intersubject communications; chain reaction; atom; chlorine; molecule; light; neutron; radical; synthesis